Unpacking older drivers’ maneuver at intersections: Their visual-motor coordination and underlying neuropsychological mechanisms - Sun, Q.; Xia, Jianhong (Cecilia); Li, Y.; Foster, Jonathan; Falkmer, Torbjorn; Lee, H. (Pergamon, 2018)
© 2018 Elsevier Ltd. Background: Negotiating intersections is one of the principal concerns for older drivers as it requires precision and efficiency in visual-motor coordination (VMC). The complex intersection manoeuvre places high demands on visual perception, attention, motor control and executive functioning. Understanding the relationship between VMC and cognitive abilities in older drivers is important, but yet to be systematically explored. Methods: We recorded 38 older adults’ driving manoeuvre at intersections using eye tracking and advanced surveying positioning technologies. VCM performance of the participants were indexed using multiple parameters of visual and motor behaviors with a Data Envelopment Analysis (DEA) model. Participants also performed a battery of cognitive tests of visual attention, spatial abilities, visual-motor speed and executive functions. Results: Significant correlations were identified between VMC performance and eight cognitive measurements: UFOV 2 and 3, Block Design, Benton's JLO, D-KEFS TMT 1, 2, 3 and 4. Cognitive tests measuring selective attention, spatial ability and executive function were found to be the best predictors for VMC performance. Conclusions: Specific cognitive abilities in older drivers were associated with poorer VMC at intersections. VMC assessment can be used to identify risky older drivers and their problematic behaviors. In the future, tailored VMC evaluations and intervention programs may be developed to improve older drivers’ safety behind the wheel.